Pengaruh Strategi Komunikasi Guru Berbasis Media Gadget di Masa Covid- 19 terhadap Motivasi Belajar Siswa - Badruddin Kaddas; Riska Sri Wahyuni (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2022)
Abstract: The effect of gadget media-based teacher communication strategies in the covid 19 period on student learning motivation. This study aims to determine the communication of gadget media-based teachers during the Covid-1 9 period on student learning motivation. This research uses a quantitative approach with aquasi-experimental research research. The population in this study was grade V students of SD Negeri Pacinang Makassar, the essay used in this study was the Pre-test Post-test nonequivalent control group design. Research instruments in the form of questionnaires, student observation sheets, and documentation to test hypotheses using paired sample t-tests. Data analysis is carried out by analysis of descriptive statistical data and inferential statistics. The results of the study in the control class obtained an average pretest value of 51.15 while the average posttest value of 58.45 was still lower than the experimental class. The average score of the experimental class in the pretest was 84.35 while the posttest value was 89.50. Based on the results of the hypothesis test, it is known that the paired t-test results obtained by the level of Sig. (2-tailed) of 0.000< 0.05. Thus, it can be seen that there is an influence of media g-adget teacher communication strategies during the Covid-19 period on student learning motivation.